The Role of Perceived Organizational Support Mediation on the Relationship between Job Satisfaction and Organizational Commitment in the Public Sector - Rahmatasya, Mellyca; Mulyana, Olievia Prabandini (Universitas Pamulang, 2025)
This study aims to analyze the mediating role of perceived organizational support in the relationship between job satisfaction and organizational commitment among public sector employees. The background of this research arises from the phenomenon of disparities in employees’ attachment and loyalty, despite some exhibiting high levels of job satisfaction, highlighting the need to understand the psychological mechanisms linking job satisfaction to organizational commitment. This study employed a quantitative correlational survey design involving 120 employees with a minimum tenure of one year. Data were collected using the Job Satisfaction Survey, the Survey of Perceived Organizational Support, and the Organizational Commitment Questionnaire. Analysis was conducted using PROCESS Macro Model 4 with 5,000 bootstrap samples. The results show that job satisfaction significantly predicts POS (β = 0.32, p < 0.001), and POS significantly predicts organizational commitment (β = 0.37, p < 0.001). Job satisfaction also exerts a significant direct effect on organizational commitment (β = 0.28, p < 0.001). The indirect effect through POS is 0.12, with a 95% confidence interval of 0.04–0.24, indicating partial mediation. These findings suggest that job satisfaction and perceived organizational support jointly contribute to strengthening employees organizational commitment in the public sector.